Regional value chains: Opportunities for India and ASEAN? - Saon Ray; Vasundhara Thakur (Indian Council for Research on International Economic Relations (ICRIER), 2024)
The literature on backward and forward linkages in global value chains (GVCs) explores the interconnectedness of production processes across different stages and locations within the global economy. The significance of imports in value chains, however, is relatively unexplored. Recognizing imports' role in bolstering exports can rejuvenate external demand and spur growth. To examine Indian imports from ASEAN, we utilize the ARDL bounds test for 2011-12 Q1 to 2020-21 Q2. The results reject the null hypothesis of no level relationship between ASEAN imports and other variables. Notably, the positive long-run coefficient of export logs suggests a favourable impact on Indian imports from ASEAN, while the negative COVID-19 dummy coefficient indicates pandemic-induced import setbacks.
Keywords: F14; F15; F23; 330; Imports; exports; import demand function; COVID-19; global value chains